The senior high school evening student a descriptive profile - Rausa, Lourdes M. 1944- (s.n.], 1972)
This study attempts to present a descriptive profile of the senior high school evening student. The study involved all the senior high school evening students of the Ramon Magsaysay (Cubao) High School during the school year 1971-1972. The profiles were established from results of a survey checklist, a standardized personality test, and scholastic records.